Sistem Penunjang Keputusan Untuk Rekomendasi Pemilihan Jurusan di SMK Yasbam Menggunakan Metode Simple Additive Weighting - Sopian, Muhamad; Br. Ginting, Novita; Fatimah, Fety (Jurnal Etnik: Ekonomi-Teknik, 2022)
The process of processing grades and determiningrecommendations for SMK majors is still generally done manually,while the results of the decisions must be announced on the sameday. The selection of majors at Yasbam Vocational School iscurrently through an academic test that is seen from the criteria forthe average value of report cards, TKJ theory tests, OTKP theorytests, TBSM theory tests, and specialization questionnaires.Therefore, a decision support system (SPK) is needed that can helpto solve the problem of selecting majors according to the abilities ofprospective students. This majors selection system uses the simpleadditive weighting (SAW) method for better decision making. Theresearch objectives of the decision support system for the selectionof majors at SMK Yasbam are to obtain the results of the analysisusing the SAW method, to obtain the results of the designinformation system to support the decision support for the selectionof majors at SMK Yasbam and to obtain a decision supportinformation system to recommend the selection of majors. Themethod used in this research is Research and Development. Theresults show that this system is divided by users, namely Admin andStudents. In the implementation of the Admin interface system, thereare eight menus, namely Login, dashboard, criteria data, criteriaweights, alternative data, alternative values, selection results,recommendation results, majors and users. While in the studentdesign there is an interface design, namely Login, dashboard,recommendation results. The design of this interface is based on thedesign on context diagrams, data flow diagrams and entityrelationship diagrams that have been created by applying them tothe form. Based on the test results, it was concluded that studentshad received a major recommendation from the decision supportsystem for selecting majors at SMK Yasbam using the SAW (SimpleAdditive Weighting) method.